2017
DOI: 10.3762/bjoc.13.94
|View full text |Cite
|
Sign up to set email alerts
|

Conformational study of L-methionine and L-cysteine derivatives through quantum chemical calculations and 3JHH coupling constant analyses

Abstract: The understanding of the conformational behavior of amino acids and their derivatives is a challenging task. Here, the conformational analysis of esterified and N-acetylated derivatives of L-methionine and L-cysteine using a combination of 1H NMR and electronic structure calculations is reported. The geometries and energies of the most stable conformers in isolated phase and taking into account the implicit solvent effects, according to the integral equation formalism polarizable continuum model (IEF−PCM), wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(59 reference statements)
2
1
0
Order By: Relevance
“…Although theoretical calculations indicate the conformational equilibrium of GluOMe is not very sensitive to solvent effects, the variations observed in the signal of H a upon solvent change show that the conformational equilibrium of GluOMe changes when the solvent polarity increases from CDCl 3 to DMSO. As the theoretical calculations are consistent with the results obtained in CDCl 3 , CD 2 Cl 2 , and CD 3 CN and the level of theory (ωB97X-D/aug-cc-pVTZ) used in the present study has presented coherent results for similar studied systems, the differences observed between theoretical and experimental data in DMSO can possibly be attributed to the use of an implicit solvent model in the study. It is likely that the implicit solvent model does not consider some specific interaction that occurs in GluOMe when the solvent is DMSO- d 6 .…”
Section: Results and Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Although theoretical calculations indicate the conformational equilibrium of GluOMe is not very sensitive to solvent effects, the variations observed in the signal of H a upon solvent change show that the conformational equilibrium of GluOMe changes when the solvent polarity increases from CDCl 3 to DMSO. As the theoretical calculations are consistent with the results obtained in CDCl 3 , CD 2 Cl 2 , and CD 3 CN and the level of theory (ωB97X-D/aug-cc-pVTZ) used in the present study has presented coherent results for similar studied systems, the differences observed between theoretical and experimental data in DMSO can possibly be attributed to the use of an implicit solvent model in the study. It is likely that the implicit solvent model does not consider some specific interaction that occurs in GluOMe when the solvent is DMSO- d 6 .…”
Section: Results and Discussionsupporting
confidence: 87%
“…The AcGluOMe derivative differs from GluOMe due to the presence of an amide group instead of the amine group. Most of the conformers of AcGluOMe (Figure S20) present the amide linkage anti to the C­(O)­OMe group of the backbone, which follows the same trend observed for other N -acetylated amino acid derivatives previously studied in the literature. Contrary to what was observed for the conformers of GluOMe, no conformers a are observed for AcGluOMe and thus, the conformational equilibrium of this compound is governed by only conformers that present arrangements b and c .…”
Section: Results and Discussionsupporting
confidence: 76%
See 1 more Smart Citation